Potential acceptance of COVID-19 vaccination among population residing in the urban and rural field practice areas of a tertiary care teaching hospital of West Bengal: A comparative study - Mausumi Basu; Ankita Mishra; Meghna Mukherjee; Prince Kerketta; Ratul Kumar Bysack; C. Vanlaldiki; Anamitra Chakraborty (Al Ameen Medical College, 2023)
Background: "Covishield" and "Covaxin" were the two vaccines which were approved for emergency use in India. As there is uncertainty regarding these vaccines, this study aimed to estimate the proportion of acceptance of vaccination against COVID-19 in West Bengal; to identify the possible barriers of vaccine acceptance prevalent among the study population and; to find out the association of acceptance of COVID-19 vaccination with the socio-demographic and other predictor variables. Methods: Oobservational study with cross sectional design was conductedon 294 participants in Muchisa, Budge Budge II and Ward No. 81 of Borough 10, Kolkata Municipal Corporation (KMC) selected by Stratified Random Sampling in 2021 using a predesigned, pretested and structured schedule. The statistical analysis was done using Microsoft Office Excel 2007 and Statistical Package for the Social Sciences Version 16.0. The data were explored using Pearson's chi-square test and logistic regression. A p-value of <0.05 was considered significant. Results: The potential acceptance of Covid-19 vaccination was 59.5% with higher adoption in urban population. The most potential barrier in acceptance of vaccine was "fear of side effects". Higher level of education and history of Covid-19 in the locality were associated with higher acceptance of the vaccination in both the urban and rural areas. Conclusion: A study emphasized on the need for mass campaigns and other behavior change communication activities for addressing the myths surrounding the disease and the newer vaccines and hence improving the currently low vaccine acceptance.